Cover Picture: Formation of T‐Shaped versus Charge‐Transfer Molecular Adducts in the Reactions Between Bis(thiocarbonyl) Donors and Br2 and I2 Chem. Asian J. 3/2013). Issue 3 (21st February 2013) - Mancini, Annalisa; Aragoni, M. Carla; Bricklebank, Neil; Castellano, Carlo; Demartin, Francesco; Isaia, Francesco; Lippolis, Vito; Pintus, Anna; Arca, Massimiliano
<x xml:space="preserve">Abstract</x> T‐shaped adducts …︁ …︁ of thiocarbonyl donors and dibromine are unusual compounds featuring the chalcogen atom in a hypervalent state. In their Full Paper on page 639 ff., Massimiliano Arca et al. report X‐ray diffraction, Fourier transform Raman spectroscopic, and density functional theory (DFT) investigations on the competition in the formation of T‐shaped versus charge‐transfer adducts in the reactions between a class of bis(thiocarbonyl) donors and dibromine and diiodine.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>